INDIAN TEMPLE ARCHITECTURE OF EIGHT TEMPLES OF PRACHI VALLEY OF ODISHA IN EASTERN INDIA - Mohapatra, Ratnakar; Majhi, Baikuntha (International Journal of Psychosocial Rehabilitation, 2020)
All the extant temples of the Prachi Valley possess the features of the Kalinga Style temple architecture of Odisha, which is an offshoot of the Nagara Style temple architecture of Central and North India. The earlier art historians / scholars had not dealt with the art and architecture of all the extant minor temples of the Prachi valley of Odisha in Eastern India. The Prachi valley preserves a good number of Kalinga style temples in the state of Odisha. The artistic features of some minor temples of Prachi valley really attract scholars, art historians, and archaeologists to start research works. Among the extant minor temples of Prachi valley of Odisha, some of the newly surveyed temples of different sects are taken here for our discussion. The names and sites of these minor temples of the Prachi Valley are 1. Purneshvara temple at Niali, 2. Balunkeshvara temple at Anlo, 3. Jogeshvara temple at Jogesvarpur,4. Kakatei Temple at Kakatpur, 5. Chandaghanta Chamunda Temple at Nuagaon, 6. Charchika temple at Narasinghpurhat, 7. Brahma temple at Niali, and 8. Veer Hanumana temple at Badajharilo. The aim of this article is to focus on artistic features, architectural patterns along with the religious significance of above eight minor temples of the Prachi valley of Odisha in Eastern India. Methodologically, both the primary and secondary sources have been used for the writing of the present article.